Reformasi Pertanggungjawaban Perdata Pada Transaksi Digital Berbasis Kecerdasan Buatan - Alifah Nur’Aini; Vido Abivandya Kusuma Putra; Nazhifa Septia Rahmadani (Indo Publishing, 2025)
The rapid advancement of Artificial Intelligence (AI) technology has transformed the landscape of legal interactions, particularly in the execution of digital transactions through smart contracts. However, the Indonesian Civil Code (KUH Perdata), rooted in classical legal principles, has yet to adapt to the emergence of autonomous AI systems capable of performing legal actions independently. This research aims to analyze the normative vacuum in civil liability regulation concerning AI-based transactions and to formulate a reform of the civil law doctrine that aligns with the digital era. Using a normative legal research method with statutory, conceptual, and comparative approaches, this study examines classical civil law doctrines (Salim H.S, 2018; Subekti, 2014; Prodjodikoro, 2011) and progressive legal theories (Sanusi, 2025). The findings indicate that the traditional fault-based liability principle is no longer sufficient to address issues arising from autonomous AI actions, as such systems operate without human intent or volition. Therefore, strict liability and joint liability frameworks are more appropriate for determining responsibility for damages caused by AI operations. Furthermore, integrating civil and cyber law through the concept of cyber civil law (Rosadi & Yulianti, 2020) is necessary to ensure adaptive legal certainty in digital environments. In conclusion, reforming the doctrine of civil liability is essential to establish a fair, responsive, and future-oriented legal framework that protects individuals and ensures justice in the age of artificial intelligence.